2019
DOI: 10.3390/cells8101117
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Human and Mouse Biliary Epithelial Cell Gene Profiles

Abstract: Background: Chronic liver diseases are frequently accompanied with activation of biliary epithelial cells (BECs) that can differentiate into hepatocytes and cholangiocytes, providing an endogenous back-up system. Functional studies on BECs often rely on isolations of an BEC cell population from healthy and/or injured livers. However, a consensus on the characterization of these cells has not yet been reached. The aim of this study was to compare the publicly available transcriptome profiles of human and mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Parenchymal hepatocytes comprise up to 85% of the liver volume, with sinusoidal endothelial cells, perisinusoidal stellate cells and phagocytic Kupffer cells, with intrahepatic lymphocytes making up the rest. Strong evidence suggests that different hepatic cell types possess variable gene expression profiles [6][7][8]. The liver is therefore highly heterogeneous in both gene expression and metabolic function.…”
mentioning
confidence: 99%
“…Parenchymal hepatocytes comprise up to 85% of the liver volume, with sinusoidal endothelial cells, perisinusoidal stellate cells and phagocytic Kupffer cells, with intrahepatic lymphocytes making up the rest. Strong evidence suggests that different hepatic cell types possess variable gene expression profiles [6][7][8]. The liver is therefore highly heterogeneous in both gene expression and metabolic function.…”
mentioning
confidence: 99%
“…Therefore, we investigated the gene expression of a large set of quiescent and activated liver progenitor cell (LPC) and biliary epithelial cell (BEC) markers. These LPCs and BECs are endogenous cells that are known to differentiate into hepatocytes and cholangiocytes, and frequently accompany chronic liver diseases ( Figure 5 A) [ 30 ]. In this context, we found that the gene expression of the LPC/BEC markers Atf3 (19-fold), Cyr61 (7-fold), Ddr1 (6-fold), Elovl7 (38-fold), Glis3 (8-fold), and Hspa1a (6-fold) was significantly increased more than 5-fold in Fah-deficient livers when NTBC therapy was discontinued for seven consecutive days using microarray analyses ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…To support this, we compared the LPC/BEC marker expression profile of liver tissue derived from NTBC-treated Fah-deficient mice and those that were deprived from NTBC for seven days. This gene expression profile was previously established using meta-analyses of human and mouse biliary epithelial cell gene profiles [ 30 ] and allowed us to discriminate between the two experimental groups. More specifically, we found that the gene expression of several LPC/BEC markers including Atf3 , Cyr61 , Ddr1 , Elovl7 , Epcam , Glis3 , and Hspa1a was highly increased in Fah-deficient livers when NTBC therapy was discontinued for seven consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether the genes that behave opposite between in vitro and 8 in vivo activation are enriched in an HSC subpopulation, we computed the overlap of our gene list 9 (Suppl. Table 3) with the single cell data by Krenkel et al (GSE132662) as described before [6,19,20].…”
Section: Western Blotting 11mentioning
confidence: 99%
“…In brief, raw data files were downloaded from NCBI (https://www.ncbi.nlm.nih.gov/geo) and imported 11 into RStudio (https://www.rstudio.com). Gene signature scores were computed by Single-Cell Signature 12 Score in Linux and using Single-Cell Signature Merger and Single-Cell Signature Viewer the signature 13 scores could be visualized on UMAP plots [19,20].…”
mentioning
confidence: 99%